PENGEMBANGAN MULTIMEDIA INTERAKTIF UNTUK MATA PELAJARAN ILMU PENGETAHUAN SOSIAL (IPS) SEKOLAH DASAR KELAS V - Basori, Muhamad (Universitas Nusantara PGRI Kediri, 2016)
Abstract: The research aimed to: (1) develop an interactive multimedia as learningmedia of social studies for fifth grade students with the materials of events aroundproclamation; and (2) find the product eligibility from the aspect of material, appearance,and attractiveness for the learning of elementary school social studies. The research wasconducted through several stages. The first stage was introduction that included librarystudy and field study. The second stage was development that included initial productplanning and development. The third stage was field testing that included preliminary fieldtest, main field test and operational field test. The results of validation conducted by mediaexpert and material expert showed that the eligibility of learning multimedia for socialstudies on the aspect of media was 4.23 (very good) and the eligibility of learningmultimedia for social studies on the aspect of material was 4.26 (very good). The results offield testing showed that the students’ response toward the multimedia eligibility was 4.08(very good). These results showed that the learning multimedia for social studies waseligible to be implemented in the learning activities and might become an alternative ofsocial studies learning resource especially for the fifth grade students with materials ofevents around proclamation. Abstrak: Penelitian ini bertujuan untuk: (1) mengembangkan multimedia interaktif sebagaimedia pembelajaran IPS kelas V dengan materi peristiwa sekitar proklamasi dan (2)mengetahui kelayakan produk dari aspek materi, aspek tampilan dan aspek kemenarikanuntuk pembelajaran IPS SD. Dilaksanakan melalui beberapa tahapan, tahap pertama adalahpendahuluan yang meliputi studi pustaka dan studi lapangan, tahap kedua pengembangan yang meliputi perencanaan dan pengembangan produk awal. Tahap ketiga uji lapanganmeliputi uji coba preliminary field test, main field test dan operational field test. Hasilvalidasi oleh ahli media dan ahli materi menunjukkan bahwa kelayakan multimediapembelajaran IPS pada aspek media sebesar 4,23 (sangat baik) dan kelayakan pada aspekmateri sebesar 4,26 (sangat baik). Hasil uji coba lapangan menunjukan bahwa tanggapansiswa terhadap kelayakan multimedia dengan rerata skor 4,08 (baik). Hasil tersebutmenunjukkan bahwa multimedia pembelajaran IPS yang dikembangkan layak digunakandalam kegiatan pembelajaran dan menjadi alternatif sumber belajar IPS khususnya siswakelas V dengan materi peristiwa sekitar proklamasi.